Errors Analysis of Students’ Pronunciation in Pronouncing English Vowels and Consonants at Second Semester Class A2 of Batanghari University - Dwi Yul Maulina; Wennyta Wennyta (JELT: Journal of English Language Teaching, 2021)
This research aimed to find out what vowel and consonant sound are difficult to be pronounced by the students at the second semester class A2 of Batanghari University. This research is done in the form of sound recording. It employed a qualitative method that consisted of two kinds of test, there were text that consisted one paragraph and word list that include 86 items. The subject of the research was the second semester class of Batanghari University in academic year 2020 namely class A2 that consisted of 17 students. The data were collected through text and word list, and were analyzed qualitatively. The result of the research showed that the students at second semester class A2 of Batanghari University got some English vowel and consonant difficult to pronounce. The result showed that, the English vowel sound which difficult to pronounce by the students are: /ɪ/, /e/, /ɒ/, /˄/, /Ʊ/, /Ȝ:/, /ə/, /i:/, /u:/, /ɔ:/, /eə/, /eɪ/, /əƱ/, /aƱ/, /ɔɪ/, /ɪə/, /eə/ and /Ʊə/. There were ninety occurances of errors in pronouncing vowels made by the students by listen their sound record. And the English consonant sound which difficult to pronounce by the students are: /k/, /tʃ/, /f/, /s/, /ʃ/, /h/, /d/, /dȜ/, /v/, /Ȝ/, /m/, /n/, /ƞ/ and /w/. It was known that there were thirthy-eight occurances of error in pronouncing consonants made by the students. The higher percentage in symbol /ɪ/ with 13,28%, the errors happened in seventeen times. And the lower percentage is 0,78%, the errors happened in once in each symbol. It seen in symbol /Ȝ:/, /eə/, /eɪ/, /ɪə/, /f/, /s/, /ʃ/, /d/, /Ȝ/, and /w/. The students still make errors that caused by their first language or their mothertongue, language background of the students and learning process.Key Words: Error Analysis, Pronunciation, English Vowels and Consonants